Nilai Cerna dan Biodegradasi Theobromin Pod Kakao dengan Perlakuan Fermentasi Menggunakan Inokulum Multi Mikrobia - Suci Wulandari; Ali Agus; Mohamad Soejono; Muhammad Nur Cahyanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2014)
In the recent years it has been reported that there is a multimicrobe culture which is used for fermentation of feed ingredients and complete feeds. This multi microbial culture is introduced by the name of SBP® (Saus Burger Feed). This research study aims to understand the influence of fermented cocoa pod using multi microbe which is contained in the SBP to digest and biodegrade theobromine in the cocoo pod. Cocoa pod was fermented under anaerobic conditions at room temperature. Inoculums levels which were added consist of 0; 0,05, and 0,1% respectfully. During fermentation of the cocoa pod, its samples were taken on days of 0, 3, and 6, to understand the bacterial growth, pH changes, and changes in digestibility, and biodegradation of theobromine. Furthermore, it was followed by the isolation of bacteria, to understand the characteristics of obtained bacterial isolates, and fermented cocoa pod by way of isolates, and tested its ability in producing the cellulase enzyme (CMC-ase and β-glucosidase), and its ability to degrade the theobromine. The research results showed that during fermentation of cocoa pod there were increasing of lactic acid bacteria population, and total bacteria, decreasing in the pH, increasing in the fiber digestibility, and decreasing in content of theobromine in the cocoa pod. Changes in these parameters, more real case, and the cocoa pod is fermented with a moisture content of 40% and inoculated with a dose of 0,05% SBP® with a long fermentation of 6 days. Decreasing in the fermentation of theobromine in the cocoo pod with the largest reaching of 17,02%. Increasing in the fiber digestibility, and decreasing in the content of theobromine, during fermentation of cocoa pod by inoculants SBP, it is confirmed with characteristic of bacterial isolates which is obtained from the fermented cocoa pod. There were 8 isolates of bacteria, which can produce CMC-ase enzyme, and β-glucosidase with the different level of production. Several bacterial isolates were also able to reduce the content of theobromine, in liquid culture, up to 27,07%. ABSTRAKBeberapa tahun terakhir telah diberitakan adanya kultur multi mikrobia yang dipergunakan untuk fermentasi bahan pakan dan complete feed. Kultur multi mikrobia ini dikenalkan dengan nama Saus Burger Pakan® (SBP®). Penelitianini bertujuan untuk mengetahui pengaruh fermentasi pod kakao menggunakan multimikrobia yang terkandung dalam SBP terhadap nilai cerna serat dan biodegradasi theobromin. Pod kakao difermentasi dalam kondisi anaerob pada suhu ruang. Kadar inokulum yang ditambahkan adalah 0; 0,05; dan 0,1 %. Selama fermentasi dilakukan pengambilan sampel pada hari ke-0, 3, dan 6 untuk mengetahui pertumbuhan bakteri selama fermentasi pod kakao, perubahan pH, perubahan nilai cerna, dan degradasi theobromin selama fermentasi, kemudian dilanjutkan dengan isolasi bakteri untuk mengetahui karakteristik isolat bakteri dari pod kakao terfermentasi dengan cara isolat yang diperoleh diuji kemampuannya dalam menghasilkan enzim selulase (CMC-ase dan βglukoseidase) dan kemampuannya dalam mendegradasi theobromin. Hasil penelitian menunjukkan bahwa selama fermentasi pod kakao terjadi kenaikan populasi bakteri asam laktat dan bakteri total, penurunan pH, kenaikan nilai cerna serat, dan penurunan kandungan theobromin dalam pod kakao. Perubahan parameter tersebut lebih nyata terjadi pada pod kakao yang difermentasi dengan kadar air 40% dan diinokulasi dengan SBP® dosis 0,05% dengan lama fermentasi 6 hari. Penurunan theobromin pada pod kakao fermentasi terbesar mencapai 17,02%. Kenaikan nilai cerna serat dan penurunan kandungan theobromin selama fermentasi pod kakao oleh inokulan SBP dikonfirmasi dengan karakteristik isolat-isolat bakteri yang diperoleh dari pod kakao yang terfermentasi. Ada 8 isolat bakteri yang mampu menghasilkan enzim CMC-ase dan β-glukosidase dengan tingkat produksi yang berbeda-beda. Beberapa isolat bakteri juga mampu menurunkan kandungan theobromin dalam kultur cair sampai sebesar 27,07%.